Compliance model of Exechon manipulators with an offset wrist. (January 2022) - López-Custodio, P.C.; Fu, R.; Dai, J.S.; Jin, Y.
Abstract: The stiffness of the Exechon hybrid manipulator is a crucial performance indicator as the manipulator is used as a 5-axis machine tool. Normally, the serial module of the Exechon is not included in the kinematic and stiffness analysis. In terms of kinematics, the parallel and serial modules are said to be decoupled, i.e. parallel module can be solved for position and the serial module can be used to compensate the parasitic orientation of the parallel platform. This is only possible when the serial module is a perfect spherical wrist. However, several models of Exechon technology have an offset wrist rather than a spherical one. Such an offset makes it impossible to obtain a kinematic decoupling. In all publications available in the literature, the Exechon is considered to have a perfect spherical wrist. Therefore, this paper presents the inverse kinematics and compliance model of Exechon manipulators with offset wrists. The unknown coefficients in the compliance model are determined by optimizing the model against experimental data. The resulting predictions are then compared against more experimental results to validate the model. Highlights: The inverse kinematics of the Exechon with offset wrist is solved for the first time. The compliance model of the Exechon is obtained considering both modules. The compliance is obtained using an optimization process and experimental data. This method can be used when the detailed structure of the robot is not fully known. The model is compared against experimental values at several points of the workspace.